2019
DOI: 10.1097/bco.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Increasing number of fibroblast, capillary and collagen amount in Achilles tendons of rats with diabetic mellitus after application of stromal vascular fraction derived from adipose tissue

Abstract: Background: Achilles tendinopathy is common in diabetes mellitus and makes the tendon susceptible to rupture. Achilles tendon rupture healing is impaired in diabetics. Stromal vascular fraction can be an alternative treatment for Achilles tendon rupture in diabetic tendinopathy. Methods: Eighteen rats were used in this experimental study and divided into three groups: group 1, normoglycemia; group 2, diabetes mellitus; and group 3, diabetes mellitus inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The repair and regenerative capacity of diabetic tendons is compromised during the healing process after injury. Fibroblast proliferation[ 43 , 44 ], vascularity[ 21 , 44 , 45 ], and collagen levels[ 36 , 44 ] were reduced in injured diabetic tendons during healing. Egemen et al [ 43 ] showed that although similar collagen deposition and vessel proliferation were observed in both injured diabetic and nondiabetic tendons during healing, lymphocyte infiltration and osteochondroid metaplasia of some tenocytes were observed in the injured diabetic tendons.…”
Section: Histopathological Alterations In Diabetic Tendinopathymentioning
confidence: 99%
“…The repair and regenerative capacity of diabetic tendons is compromised during the healing process after injury. Fibroblast proliferation[ 43 , 44 ], vascularity[ 21 , 44 , 45 ], and collagen levels[ 36 , 44 ] were reduced in injured diabetic tendons during healing. Egemen et al [ 43 ] showed that although similar collagen deposition and vessel proliferation were observed in both injured diabetic and nondiabetic tendons during healing, lymphocyte infiltration and osteochondroid metaplasia of some tenocytes were observed in the injured diabetic tendons.…”
Section: Histopathological Alterations In Diabetic Tendinopathymentioning
confidence: 99%